Industrial Crisis and the Open Economy - Underhill, G. author. aut Link
XVIII, 280 p.
Keywords: Written in the context of contemporary theoretical debate in international political economy, this book overturns a number of myths about the political economy of trade in one of the oldest areas of industry. In this way the author systematically links the changing characteristics of the trade regime to structural change and adjustment in global industry. He argues that state policy processes, international regimes and the industrial adjustment strategies of firms must be conceptualised as integrated processes of governance cutting across levels of analysis in the global political economy.